Cardiovascular risk in patients with psoriasis-relationship with oxidative stress and dyslipidemia - Karanikolic, Vesna; Bakic, Mirjana; Gluscevic, Sanja; Mercantepe, Filiz; Klisic, Aleksandra (Journal of Medical Biochemistry, 2025)
Background: Patients with psoriasis are at an increased risk of cardiovascular disease (CVD). Psoriasis and atherosclerosis share the common soil of inflammation and oxidative stress in their pathogenesis. The current study aimed to examine cardiovascular risk in relation to some non-traditional (i.e., biomarkers of oxidative stress and inflammation) and traditional metabolic parameters in patients with psoriasis. Methods: A total of 68 (57% men) patients with psoriasis were included. Traditional metabolic parameters, markers of oxidative stress [i.e., oxidation protein products (AOPP), malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD)] and inflammation (C-reactive protein) were measured. The atherosclerotic cardiovascular disease (ASCVD) risk score was used to measure CVD risk. Patients were divided into ASCVD score tertiles.Results: Patients with a higher ASCVD score had significantly lower high-density lipoprotein cholesterol (HDL-C), higher triglycerides (TG), and higher TG/HDL-C ratio (p for trend p
Keywords: cardiovascular risk; inflammation; oxidative stress; psoriasis